Eco-friendly and Cost-Effective Methods of Pasteurization of Substrates for Oyster Mushroom Cultivation - Jeet, S.; Mehta, S. K.; Chugh, R. K.; Raj, K. (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted during October, 2020−March, 2021 at Mushroom Technology Laboratory, Department of Plant Pathology, Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana, India to find out the effects of solar heat and hot-water on pasteurization of substrates. A significant maximum temperature of 59.9°C was recorded in wheat substrate of 2.0' heap height covered with black polythene sheet for 6 h. A maximum temperature of 48.0°C was recorded in solar heat treatment of substrates for 6 h. The main aim of pasteurization is to reduce harmful microflora on substrates. The least bacterial colonies at 6.7×109 cfu g-1 substrate were recorded in wheat substrate of 2.0' heap height covered with black polythene sheet for 6 h and the highest at 9.4×109 cfu g-1 in paddy straw of 1.0' heap height uncovered for 2 h. The minimum fungal colonies at 4.7×104 cfu g-1 were recorded in wheat substrate of 2.0' heap height covered with black polythene sheet for 6 h followed by 4.9×104 cfu g-1 in paddy straw. A maximum number of fungal colonies at 6.9×104 cfu g-1 were seen in wheat straw of 1.0' heap height uncovered for 2 h. In hot-water treatment, the minimum bacterial colonies at 3.7×109 cfu g-1 substrate and fungal colonies at 1.9×104 cfu g-1 substrate were observed in wheat substrate treated at 70°C for 20 m followed by bacterial colonies at 4.3×109 and fungal colonies at 2.1×104 cfu g-1 in hot-water treated paddy substrate at 70°C for 20 m.